Characterization of the complete mitochondrial genome sequence of Neoscona scylla and phylogenetic analysis. Issue 1 (2nd January 2019) - Xu, Kangkang; Lin, Xinchi; Yang, Daxing; Yang, Wenjia; Li, Can
Abstract: The complete mitochondrial genome of the orb-weaving spider Neoscona scylla was characterized in this study. The circular molecule is 14, 092 bp in length (GenBank accession no. MK086023), containing 13 protein-coding genes (PCGs), two ribosomal RNA (rRNA) genes, 22 transfer RNA (tRNA) genes, and a control region. The nucleotide composition is asymmetric (35.27% A, 9.82% C, 15.55% G, 39.36% T), with an overall A + T content of 74.63%. The gene arrangement of N. scylla is identical to that observed in other spiders. Nine PCGs are initiated with typical ATN start codons, three genes ( cox2, cox3, and nad6 ) begin with TTG, and cox1 use TTA as initiation codon. Twelve PCGs stop with complete termination codon TAA and TAG, while nad3 uses incomplete termination codon (T). Twenty-five reading frame overlaps and five intergenic regions are found in the mitogenome of N. scylla . Seven tRNAs lose TΨC arm stems, whereas three lack the dihydrouracil (DHU) arm. The phylogenetic relationships based on 13 PCGs show that N. scylla clusters closest to 5 species of Araneidae.